Pendampingan Pembelajaran Yanbu’a dalam Meningkatkan Kualitas Tajwid Santri di TPQ Haniful Ulum - Mohamad Madum; Fitrotin Azizah; Meilinda Putri; Muhammad Syafi Syafiq (Mafapress Institut Pesantren Mathali'ul Falah Pati, 2025)
This community service activity has an impact on improving the implementation of Yanbu'a method learning assistance in improving the ability to apply tajwid to students at TPQ Haniful Ulum. Rahayu Village. TPQ Haniful Ulum is a Quranic education institution serving students from early childhood to adolescence, yet it still faces challenges in achieving correct Tajweed Reading standards. The approach used in this study is participatory action research (PAR). The results show that the Yanbu’a learning method is mentored gradually and systematically through Reading habituation, repetition, and direct teacher correction. The students’ response and enthusiasm towards this method is very positive, reflected in increased participation and eagerness to learn. The teachers also demonstrate active involvement in the mentoring process. There has been a significant improvement in students’ tajweed skills, particularly in letter articulation, the length of recitation (mad), and Reading rules. The factors supporting the success of this mentoring include the availability of Yanbu’a books, teacher commitment, and a conducive learning environment. Meanwhile, the inhibiting factors include limited time, a limited number of teachers, and variations in students’ ability levels in applying Tajweed. In conclusion, mentoring the Yanbu’a learning method, delivered consistently and intensively, can enhance students’ skills in applying tajweed at TPQ Haniful Ulum. To maintain and improve the results achieved, it is necessary to strengthen teacher capacity and increase supporting facilities.